Contract, cooperation, and performance in international joint ventures - Luo, Yadong (Strategic Management Journal, 2002)
Abstract This study examines how contract, cooperation, and performance are associated with one another within international joint ventures (IJVs). We argue that contract and cooperation are not substitutes but complements in relation to IJV performance. An IJV contract provides an institutional framework guiding the course of cooperation, while cooperation overcomes the adaptive limits of contracts. Our analysis of 293 IJVs in a dynamic market demonstrates that previous cooperation bolsters contractual adaptability, which in turn nurtures current cooperation between the same partners. We find that contract completeness and cooperation drive IJV performance both independently and interactively. When contracts are more complete, cooperation contributes more to performance. Contract and cooperation differ in their quadratic effects such that the contribution of contract completeness to performance declines as completeness increases but the contribution of cooperation remains linear. Copyright © 2002 John Wiley & Sons, Ltd.